Assessment of Financial Factors Affecting Insurance Penetration in Nakuru Town, Kenya - Njuguna, G. W.; Kimani, Elijah M. (My University, 2016)
Over the past decade, insurance and banking firms have undergone transformation in the manner they offer their products and services in a bid to remain relevant in the insurance industry. Kenya, just like many developing countries is still at the infancy stages of absolute insurance cover. Records indicate that majority of Kenyans are presently not under any insurance cover. The study assessed the effect of financial factors on insurance penetration in Nakuru town, Kenya. The financial factors examined included administrative costs and agency costs. Blau administrative cost theory, agency theory, and S-curve theory guided the study. This study adopted a cross-sectional survey research design. The study focused on the 417 employees working with insurance firms in Nakuru town. A sample of 61 respondents was selected using stratified random sampling method. The study used a self-administered semistructured questionnaire to collect data. The research questionnaire was pilot tested. Data analysis constituted both descriptive statistics and inferential statistics. Descriptive statistics included means, modes and standard deviations. Inferential statistics included Pearson’s Product Moment Correlation and multiple regression analysis. Findings were presented in tables. The study found that all the financial factors investigated had significant relationship with insurance penetration. The study concluded that insurance firms incur administrative and agency costs that hamper insurance penetration. The study recommended that insurance firms need to arrest escalating costs associated with administrative functions and agency.
Keywords: Administrative costs; agency costs; financial factors; insurance firms; insurance penetration